2009
DOI: 10.2514/1.43848
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Supersonic Combustion in Three-Dimensional Configurations

Abstract: A turbulence model that calculates the turbulent Prandtl and Schmidt numbers as part of the solution, addresses turbulence/chemistry interactions, and accounts for compressibility effects is used to simulate supersonic combustion in two three-dimensional experiments: the SCHOLAR experiment, which employs vitiated air and hydrogen fuel, and the HyShot experiment, which employs air and hydrogen fuel. Two chemical kinetic models are employed: one employs reaction rates that are functions of temperature, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In particular, if a constant Schmidt number assumption is pursued, there is much uncertainty about the correct value of S c t having to be assigned. 64,65 On the other hand, several variable Schmidt and Prandtl number models have been proposed, 6669 although each is formulated and calibrated concerning specific fields of applications. In particular, Xiao et al 66 derived a complete turbulence model which accounts for variable turbulent Prandtl, P r t, and Schmidt, S c t, numbers relying on the introduction of additional transport equations for the variance of enthalpy and concentrations and their dissipation rates.…”
Section: Selection Of Sub-grid Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, if a constant Schmidt number assumption is pursued, there is much uncertainty about the correct value of S c t having to be assigned. 64,65 On the other hand, several variable Schmidt and Prandtl number models have been proposed, 6669 although each is formulated and calibrated concerning specific fields of applications. In particular, Xiao et al 66 derived a complete turbulence model which accounts for variable turbulent Prandtl, P r t, and Schmidt, S c t, numbers relying on the introduction of additional transport equations for the variance of enthalpy and concentrations and their dissipation rates.…”
Section: Selection Of Sub-grid Modelsmentioning
confidence: 99%
“…In particular, Xiao et al 66 derived a complete turbulence model which accounts for variable turbulent Prandtl, P r t, and Schmidt, S c t, numbers relying on the introduction of additional transport equations for the variance of enthalpy and concentrations and their dissipation rates. Although the model was successfully tested against experiments involving supersonic mixing and combustion, 67 formulating additional transport equations requires ad hoc calibration of a large number of modeling constants based on the test case under consideration. Conversely, Goldberg et al 68 proposed a fully algebraic formulation to approximate the spatial distribution of P r t and S c t, which merely takes into account the chemical species characterized by the maximum gradient at a specific location in the case of a multi-species flow test case.…”
Section: Selection Of Sub-grid Modelsmentioning
confidence: 99%
“…Xiao et al 14 have also validated variable Schmidt number formulation for Scramjet applications through 2D simulations. Keistler et al 15 have used models for the prediction of turbulent Prandtl/ Schmidt numbers for simulations of supersonic combustors from two different experiments (SCHOLAR and HyShot). Comparisons were made with available measurements of pressure temperature and composition, and fair to good agreement was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The fuel must be injected, mixed with the air, and burned within such a short time. Therefore the interaction among shock wave, turbulence and chemical reaction [2][3][4] makes the flow to be a complicated multi-scale phenomenon characterized by a wide range of length and time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work [3][4][5][6][7][8] has already indicated that supersonic internal flows are characterized mainly by streamwise vorticity and thus by maximum helicity( Hv  ). In the low speed incompressible flow, the Kolmogorov scale divides the flow into two ranges 9 : the inertial subrange and the viscous subrange.…”
Section: Introductionmentioning
confidence: 99%